2022
DOI: 10.3389/fpls.2022.788828
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Differences in Anthocyanin Accumulation in Cotton (Gossypium hirsutum L.) Induced by Red and Blue Light

Abstract: Many factors, including illumination, affect anthocyanin biosynthesis and accumulation in plants. light quality is the key factor affecting the process of photoinduced anthocyanin biosynthesis and accumulation. We observed that the red color of the Upland cotton accession Huiyuan with the R1 mutation turned to normal green color under light-emitting diodes (LEDs), which inspired us to investigate the effect of red and blue lights on the biosynthesis and accumulation of anthocyanins. We found that both red and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…Although flavonoid pathway was generally less active in H-7d samples compared with that of H-4d, the levels of PAs and anthocyanins were still increased as the salinity treatment prolonged ( Figure 4B ). This phenomenon might be partially attributed to the up-regulation of genes within the flavonoid pathway, as well as the enhanced transcription of genes related to photosynthesis, which produces precursors for flavonoids ( Shao et al., 2022 ). In addition to the biological processes and pathways mentioned above, both GO and KEGG analyses suggested that transcription factors (TFs) were also enriched in the DEGs whose expression were affected by the duration of H stress ( Figure 8E ).…”
Section: Resultsmentioning
confidence: 99%
“…Although flavonoid pathway was generally less active in H-7d samples compared with that of H-4d, the levels of PAs and anthocyanins were still increased as the salinity treatment prolonged ( Figure 4B ). This phenomenon might be partially attributed to the up-regulation of genes within the flavonoid pathway, as well as the enhanced transcription of genes related to photosynthesis, which produces precursors for flavonoids ( Shao et al., 2022 ). In addition to the biological processes and pathways mentioned above, both GO and KEGG analyses suggested that transcription factors (TFs) were also enriched in the DEGs whose expression were affected by the duration of H stress ( Figure 8E ).…”
Section: Resultsmentioning
confidence: 99%
“…Differential analysis of three groups was performed using DESeq2 [ 29 ] to identify DEGs. The false discovery rate ( FDR ) correction p -value was calculated using the Benjamini-Hochberg method, and DEGs were identified according to FDR ≤ 0.05 and |log2 fold change| ≥ 1.0 [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Differential analysis of three groups was performed using DESeq2 (Love, et al 2014) to identify DEGs. The false discovery rate (FDR) correction p-value was calculated using the Benjamini-Hochberg method, and DEGs were identi ed according to FDR ≤ 0.05 and |log2 fold change| ≥ 1.0 (Shao, et al 2022).…”
Section: Transcriptome Analysis Of Differentially Expressed Genes (Degs)mentioning
confidence: 99%